Inherent vice [videorecording (DVD)] - Anderson, Paul Thomas; Phoenix, Joaquin; Brolin, Josh; Wilson, Owen, 1968-; Witherspoon, Reese, 1976-; Pynchon, Thomas (Warner Home Video, 2015)
Private eye Doc Sportello's ex-old lady shows up with a story about her current billionaire land developer boyfriend whom she just happens to be in love with, and a plot by his wife and her boyfriend to kidnap that billionaire and throw him in a loony bin.